Ab initio calculations of partial molar properties in the single-site approximation - Ruban, A.V.; Skriver, H.L.
We discuss the application of the single-site approximation in calculations of partial molar quantities, e.g., impurity solution energy, segregation energy, and effective chemical potential, which are related to a variation of the composition of an alloy or its nonequivalent parts. We demonstrate that these quantities may be considerably in error if they are obtained in methods based on the single-site approximation for fixed alloy compositions. This error does not reflect a breakdown but rather an inappropriate use of the single-site approximation which is, in fact, found to be sufficiently accurate when properly applied in calculations of partial molar quantities.